Facile synthesis of nitrogen-doped carbon nanotubes encapsulating nickel cobalt alloys 3D networks for oxygen evolution reaction in an alkaline solution - Yu, J.; Zhong, Y.; Zhou, W.; Shao, Zongping (Elsevier SA, 2017)
© 2016 Elsevier B.V. Efficient oxygen evolution reaction (OER) catalysts are required to facilitate the large-scale exploitation of renewable energy resources and applications in electrochemical energy conversion technologies. Here, we show that metal alloy-based hybrids can provide higher electrocatalytic activity than their individual metal-based hybrids. In particular, NiCo alloys encapsulated within nitrogen-doped carbon nanotubes (NiCo@NCNTs) showed higher OER activities in an alkaline solution than the individual metal hybrids (Ni@NCNTs and Co@NCNTs), highlighting a synergy between the Ni and Co components. NiCo@NCNTs pyrolyzed at 800 °C displayed an overpotential of ~41 mV at a current density of 10 mA cm-2 and were more stable than IrO2 during 1000-cycle accelerated durability testing at a scan rate of 100 mV s-1.